Transthoracic echocardiography as a predictor of perioperative morbidity and mortality / Cheong Chao Chia - Cheong , Chao Chia (2016)
Objective: To identify risk factors (patient's characteristic, surgical and anaesthesia factors) associated to adverse outcome post-hepatectomy. Also, to assess will performing pre-operative transthoracic echocardiogram will change outcome of surgery and circumstances when pre-operative echocardiogram should be considered. Methods: This was a retrospective cohort stud done on 92 patients who have had hepatic resection surgery done under hepatobiliary surgery team from Jan 2010 to July 2016. Patient's characteristic, demographic, pre-operative echocardiography parameters such as left ventricular ejection fraction, diastolic dysfunction of left heart, left ventricular hypertrophy were assessed and associated with development of adverseevent post-op days of ventilation, hospital stay and ICU stay. Association of echocardiogram parameters were also analysed against organ failure (acute kidney failure, liver failur and major adverse cerebrovascular and cardiovascular event MACCE). Predictors contributing to adverse event post hepatectomy was analysed. Analysis method include chi square cross tabulation, non-parametric Mann Witney test, Kruskal Wallis test, and multivariate regression analysis with SPSS version 23. Result: There was no significant association when preforming pre-operative echocardiograrn or otherwise with primary outcome (development of post-operation adverse event), ICU stays or days of ventilation or any morbidity (MACCE, acute kidney failure and acute liver failure). However, if major estimated blood loss, prolonged operation time, high lactate level, perioperative pack cell transfusion, performing preoperative echocardiography become significantly related to pre-operative adverse event (p=O.O18). Conclusion: Clinical decision to perform pre-operative echocardiogram or otherwise should not be predicted based on patient's cardiac risk factor or premorbid alone. Consideration should be given to major complex hepatectomy requiring prolonged operation time, surgery with high estimated blood lost and major fluid shift. Larger prospective cohort study involving collaboration from hepatobiliary surgical team should be carried out in future.